2019
DOI: 10.2147/tcrm.s157882
|View full text |Cite
|
Sign up to set email alerts
|

<p>Chronic eosinophilic pneumonia: clinical perspectives</p>

Abstract: Chronic eosinophilic pneumonia (CEP) is an eosinophilic lung disease that is typically diagnosed by a triad of clinical symptoms including pulmonary symptoms, eosinophilia and characteristic radiographic abnormalities. It requires a high index of suspicion given its overlap with other eosinophilic conditions and lack of a specific diagnostic test. The diagnosis is made after careful consideration of other secondary causes of eosinophilia, such as infectious, drugs, or toxic etiologies. CEP generally responds r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 32 publications
1
37
0
Order By: Relevance
“…13,14 Furthermore, it is known that patients who have ILD and radiographic images with a cryptogenic organizing pneumonia or chronic eosinophilic pneumonia (COP/CEP)-like pattern often experience a relapse, particularly when corticosteroid doses are tapered or discontinued. [15][16][17] In this study, many patients who experienced a relapse had a COP/CEPlike pattern at initial ILD, suggesting that this relationship between a COP/CEP-like pattern and relapse may also be true in nivolumabinduced ILD. Therefore, it may be particularly important to monitor patients with COP/CEP-like patterns carefully, taking into consideration that they may be prone to a relapse when corticosteroid treatment is being discontinued.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…13,14 Furthermore, it is known that patients who have ILD and radiographic images with a cryptogenic organizing pneumonia or chronic eosinophilic pneumonia (COP/CEP)-like pattern often experience a relapse, particularly when corticosteroid doses are tapered or discontinued. [15][16][17] In this study, many patients who experienced a relapse had a COP/CEPlike pattern at initial ILD, suggesting that this relationship between a COP/CEP-like pattern and relapse may also be true in nivolumabinduced ILD. Therefore, it may be particularly important to monitor patients with COP/CEP-like patterns carefully, taking into consideration that they may be prone to a relapse when corticosteroid treatment is being discontinued.…”
Section: Discussionmentioning
confidence: 59%
“…This may be explained by the sustained immunostimulant effect of nivolumab 13,14 . Furthermore, it is known that patients who have ILD and radiographic images with a cryptogenic organizing pneumonia or chronic eosinophilic pneumonia (COP/CEP)–like pattern often experience a relapse, particularly when corticosteroid doses are tapered or discontinued 15‐17 . In this study, many patients who experienced a relapse had a COP/CEP‐like pattern at initial ILD, suggesting that this relationship between a COP/CEP‐like pattern and relapse may also be true in nivolumab‐induced ILD.…”
Section: Discussionmentioning
confidence: 75%
“…In recent years, several studies and case reports have demonstrated the efficacy of anti-IgE antibodies and interleukin-5/interleukin-5 receptor-alpha (IL5/IL5-Rα) antibodies in the treatment of ABPA but was more beneficial for patients with asthma than for patients with CF [ [29] , [30] , [31] , [32] ]. Mepolizumab has been successfully used to treat patients with ABPA, showing improvement in FEV1, radiographic findings, decrease in total IgE levels, and quality of life without side effects and is considered a glucocorticoid-sparing agent [ [29] , [33] , [34] , [35] , [36] , [37] , [38] , [39] ].…”
Section: Discussionmentioning
confidence: 99%
“…The phenomenon of hypereosinophilia demonstrates a direct histopathological infiltration and damage of the pulmonary interstitium. 10 Additionally, eosinophil-induced release of interferon-gamma appears to cause collagen deposition and fibrosis completely independent of lymphocytic proliferation of classical tissue remodeling. 11 Interleukins mediate the proliferation and maturation of eosinophils, which are the underlying pathological entity in ICEP and other eosinophilic diseases.…”
Section: Discussionmentioning
confidence: 99%